Satisfaction with food services: insights from a college cafeteria - Andaleeb, Syed Saad; Caskey, Ame (© 2007 Taylor & Francis Online, 2016)
This article was published in the Journal of Foodservice Business Research[©2007 Taylor & Francis Online] and the definite version is available at : http://doi.org/10.1300/J369v10n02_04 The Journal's website is at: http://www.tandfonline.com/doi/abs/10.1300/J369v10n02_04